THE ROLE OF THE INTERNAL CONTROL SYSTEM IN LIGHT OF THE ELECTRONIC OPERATION OF ACCOUNTING DATA (SOMO AS A MODEL) - Dr. Maytham Abdul-Ridha Karim; Assistant Professor Dr.Alyaa Suhail Najm (Scholars Digest Publishing, 2025)
The aim of this research is to evaluate the internal control system under electronic operating systems, to identify its essential features and role in processing electronic accounting data, and to assess its adequacy and effectiveness in detecting and preventing fraud and protecting banks from manipulation and embezzlement. It also highlights the importance of combining modern electronic systems with internal control to enhance financial and administrative performance in institutions. The research results showed a positive relationship between the level of internal control efficiency and the implementation of the electronic operating system. This means that strengthening internal control leads to improving the overall performance of the electronic system. The research also found a relationship between the efficiency of the staff and their implementation in the electronic operating system. The research also found that the electronic system detects errors in a timely manner, that adopting internal control under the electronic operating system reduces the time and effort required to carry out audits, and that adopting an electronic operating system supports the effectiveness of internal control. The study concluded that the electronic operating system helps provide accurate and appropriate information, which increases the effectiveness of the internal control process, and that the effectiveness of efficient internal control reduces errors, whether they are technical or financial. Intentional or unintentional.
Keywords: Internal control, system, electronic operations, accounting data.